2019
DOI: 10.1242/jeb.194852
|View full text |Cite
|
Sign up to set email alerts
|

The influence of added mass on muscle activation and contractile mechanics during submaximal and maximal countermovement jumping in humans

Abstract: Muscle contractile mechanics induced by the changing demands of human movement have the potential to influence our movement strategies. This study examined fascicle length changes of the triceps surae during jumping with added mass or increasing jump height to determine whether the chosen movement strategies were associated with relevant changes in muscle contractile properties. Sixteen participants jumped at sub-maximal and maximal intensities while total net work was matched via two distinct paradigms: (1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…The power model involves a large amount of muscle work (Biewener, 1998). Therefore, the observed optimal performance no longer becomes a factor of tendon storage of elastic energy and efficiency, but of single maximal force contractility of the muscle (Wade et al, 2019). Humans may have the capability to use their muscle-tendon unit in both capacities.…”
Section: Discussionmentioning
confidence: 99%
“…The power model involves a large amount of muscle work (Biewener, 1998). Therefore, the observed optimal performance no longer becomes a factor of tendon storage of elastic energy and efficiency, but of single maximal force contractility of the muscle (Wade et al, 2019). Humans may have the capability to use their muscle-tendon unit in both capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is that this is not the case in humans when jumping over these three sport surfaces. In comparison, ( Wade et al, 2019 ) recently demonstrated that adding mass during CMJ increased the time to perform the movement, resulting in lower shortening velocity of gastrocnemius lateralis and soleus muscles, and probably increasing their force and work generation without increasing mean or maximal EMG amplitude. In our study, we could speculate that surface properties tend to affect GM muscle activation level rather than altering the timing of muscle activation and/or the time to perform CMJ.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Kurokawa et al (2003) estimated that GM sarcomeres operated on favorable portion of the force-length curve (i.e., over the plateau and upper part of the ascending part) during CMJ, “where fascicles could generate more than 75% of the maximal” fascicle force ( Kurokawa et al, 2003 ). Previous findings in vertical jumping suggest that the difference in muscle architecture and function between the monoarticular soleus and the biarticular GM and gastrocnemius lateralis, both contributing to the generation of ankle power during the push-off phase of the CMJ, may result in different fascicle behavior and elastic mechanisms ( Kurokawa et al, 2003 ; Farris et al, 2016 ; Wade et al, 2019 ). It is also possible that soleus fascicle behavior was affected on the more deformable surfaces and contributed to the greater ankle plantar flexion velocity observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations